2021
DOI: 10.1183/13993003.00731-2021
|View full text |Cite
|
Sign up to set email alerts
|

Childhood asthma: pathogenesis and phenotypes

Abstract: In the pathogenesis of asthma in children there is a pivotal role for a type 2 inflammatory response to early life exposures or events. Interactions between infections, atopy, genetic susceptibility, and environmental exposures (such as farmyard environment, air pollution, tobacco smoke exposure) influence the development of wheezing illness and the risk for progression to asthma. The immune system, lung function and the microbiome in gut and airways develop in parallel and dysbiosis of the microbiome may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 171 publications
0
19
0
Order By: Relevance
“…Past research has suggested several reasons to explain the association between paternal co-residence and decreased risk of asthma. Some have suggested that environmental factors such as home allergens, community air pollution and air quality, and viral respiratory infections may be the main drivers of childhood asthma (Buteau et al, 2019; Pijnenburg et al, 2021). Paternal co-residence may improve child health through various mechanisms, including fewer living spaces and improved housing conditions, lowering the risk for additional exposures to environmental asthma triggers (Allport et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Past research has suggested several reasons to explain the association between paternal co-residence and decreased risk of asthma. Some have suggested that environmental factors such as home allergens, community air pollution and air quality, and viral respiratory infections may be the main drivers of childhood asthma (Buteau et al, 2019; Pijnenburg et al, 2021). Paternal co-residence may improve child health through various mechanisms, including fewer living spaces and improved housing conditions, lowering the risk for additional exposures to environmental asthma triggers (Allport et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In childhood, the acute upper airway infections, mainly of viral origin, represent the leading cause of asthma attacks requiring medical aid (10). Viral infections implicate bronchial inflammation that triggers airway hyperresponsiveness and further narrows the bronchial lumen (11). These phenomena depend on the overexpression of type-2 immune response usually involved in pediatric asthma.…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%
“…The former is attributed to changeable factors like inadequate adherence, while the latter persists despite addressing these factors. STRA, more common in males with atopy, exhibits eosinophilic airway inflammation and associated airway obstruction [7,8]. Severe asthma with fungal sensitization (SAFS), a sub-phenotype of STRA, is clinically more severe and resistant to steroids, often requiring maintenance oral steroid therapy [9].…”
Section: Pediatric Asthma Phenotypesmentioning
confidence: 99%